Food out of its usual rut. Carnivalesque online veganism as political consumerism - Santaoja Minna; Jallinoja Piia (Elsevier, 2022)
Food is a profoundly political issue, with themes such as environmental sustainability and ethics becoming increasingly important. These concerns have given rise to a new kind of mobilization around vegetarian and vegan eating in recent years. In-depth analyses of the characteristics of this new wave of veganism are needed. Our study explores how the new forms of carnivalesque and carefree veganism are negotiated with the older aims of veganism as political consumerism. Moreover, we aim to understand how new forms of digital food communities are built and take momentum. With these aims, we analyze a social media community for vegan food, a Finnish Facebook group called “Sipsikaljavegaanit,” Crisps and Beer Vegans (CBV). The group celebrates indulgent veganism, and by confronting several contemporary concerned food discourses related to, e.g., health, body, and gender, it has broadened the public image of veganism. We analyze indulgent veganism as a form of carnivalesque and political consumerism, taking Mikhail Bakhtin's theorization of the carnival as our analytical framework. Our analysis shows how veganism is reconfigured through various mésalliances, detaching it from previous stereotypes, and how profanation of the stereotypes differentiates between variously motivated veganisms. The carnivalesque spirit is maintained through rather heavy-handed moderation practices online, in contradiction to the idea of free communication in a public sphere. We claim that the political appeal of the new-wave veganism is in the cultivation of vitality and joy, placing serious societal concerns into the Bakhtinian genre of the serio-comical.